Development of Educational Games Based on Design Thinking to Improve Mathematical Thinking Skills - Muhtarom, Muhtarom; Sugiyanti, Sugiyanti; Zuhri, Muhammad Saifuddin; Mutiara, Nur Latifah Dwi; Adrillian, Hendrisa; Baldemor, Milagros (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
The development of technology has a significant impact on the world of education. One of them is the use of games as a learning medium. This study aims to develop an educational game integrated with a live worksheet. The development research was conducted using a design thinking approach. The design thinking stages are carried out through five steps: empathize, define, ideate, prototype, and test. The feasibility of educational games is reviewed based on expert assessments, the practicality of educational games is reviewed based on student response questionnaires, and the effectiveness of educational games is reviewed based on the results of field trials. A total of thirty students of SMP Muhammadiyah 5 Semarang became research respondents. The study results showed that educational games are feasible for mathematics learning, with an Aiken V value of 0.93. The practicality test results showed that students responded to 88.67%, with a very good category. The effectiveness test of using educational games with SPSS using the Wilcoxon Signed Test obtained a Sig. 2-tailed value of 0.000 <0.05. This shows that educational games can improve students' mathematical thinking skills in data presentation materials. This study suggests improvements in creating educational games that need to pay attention to interesting storylines and the placement of practice questions to increase students' motivation in learning mathematics.